2017
DOI: 10.1002/chem.201704546
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Substituent Variation on the Presence of Thermal Spin Crossover in a Series of Mononuclear Iron(III) Schiff Base Complexes with Terminal Pseudohalido Co‐ligands

Abstract: A series of novel iron(III) complexes of the general formula [Fe(L)X] (where L is a dianion of pentadentate Schiff base ligand N,N'-bis({2-hydroxy-3,5-dimethylphenyl}phenyl)methylidene-1,6-diamino-3-azapentane=H L1 for 1 and 2; N,N'-bis({2-hydroxy-3-ethoxyphenyl}methylidene)-1,6-diamino-3-azapentane=H L2 for 3 and 3⋅C H O) and X is terminal pseudohalido ligand (X=N for 1, X=NCS for 2, and X=NCSe for 3 and 3⋅C H O) were synthesized and thoroughly characterized. Magnetic measurements revealed the above room temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 88 publications
3
13
0
Order By: Relevance
“…The room temperature values of χ M T for 1 – 4 , which occur in the range 4.06–4.28 cm 3 K mol −1 , are consistent with the spin‐only value for HS iron(III) (χ M T ≈4.38 cm 3 K mol −1 ). They also concur with literature values in the range 3.80–4.50 cm 3 K mol −1 for closely related ferric spin‐crossover materials; although some of these reported values are somewhat low . The spin conversion in 1 – 4 , evidenced by the decrease in the values of χ M T with temperature, culminates in a plateau with a width of 115 K (140‐25 K) for 2 – 4 and 85 K (110‐25 K) for 1 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The room temperature values of χ M T for 1 – 4 , which occur in the range 4.06–4.28 cm 3 K mol −1 , are consistent with the spin‐only value for HS iron(III) (χ M T ≈4.38 cm 3 K mol −1 ). They also concur with literature values in the range 3.80–4.50 cm 3 K mol −1 for closely related ferric spin‐crossover materials; although some of these reported values are somewhat low . The spin conversion in 1 – 4 , evidenced by the decrease in the values of χ M T with temperature, culminates in a plateau with a width of 115 K (140‐25 K) for 2 – 4 and 85 K (110‐25 K) for 1 .…”
Section: Resultssupporting
confidence: 90%
“…X-band EPR spectroscopy revealed that all the complexes [Fe III (5-X-salMeen) 2 ]ClO 4 (1-4) are fully LS in frozen methanol solution at liquid nitrogen temperature and their EPR spectra are virtually indistinguishable from one another (see Experimental Sectioni nS upporting Information). LS Fe III EPR spectra tend to be either rhombic [28,35,42,49,53,60,62] or axial. [19,27,49,53,58] Those of complexes 1-4,r epresented by the spectrum of [Fe III (5-Cl-salMeen) 2 ]ClO 4 (2)[ Figure 11 b: g ?…”
Section: Solutionspin-state Equilibriamentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, when the pentadentate ligand lies in octahedral complexes, the spin crossover behavior strongly depends on the nature of the sixth simple small ligand [103]. Though plenty of pentadentate Schiff base ligands and their metal complexes have been reported [95,[104][105][106][107][108][109][110][111][112][113][114][115], the pentadentate Schiff base ligand and their metal complexes are still rare and expected to be given more attention.…”
Section: No-containing Pentadentate Schiff Base Complexesmentioning
confidence: 99%
“…24,25 Insights into spin crossover materials and their behaviour are coming from a range of techniques including magnetic data, 13,26 X-ray crystallography, 11,27 spectroscopic techniques including UV-Vis, 26,28 Resonant Ultrasound, 29 Mossbauer 11,30 and X-ray photoelectron spectroscopy. 27 Given the complexity of spin crossover behaviour, 26,31 it is important to study such systems in detail to further our understanding and allow the customised design of spin crossover materials for desired applications. Spin crossover behaviour has been identified in various Fe(II) complexes containing 3,5-bis(pyridin-2-yl)-1,2,4-triazole derivatives with trans NCS or NCSe ligands: for example, trans- 34 (pldpt = N 4pyrrol-3,5-di(2-pyridyl)-1,2,4-triazole), which has both cis and trans coordinated (2:1 ratio) NCS ligands around the Fe centre, displays interesting spin crossover behaviour.…”
Section: Introductionmentioning
confidence: 99%